2022
DOI: 10.1007/s10490-022-09834-9
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the relationship between ethnicity and depressive symptoms: The roles of climate for inclusion, job self-efficacy, and job demands

Abstract: Prior research indicates that employees from ethnic minority backgrounds are more likely to experience depression and other mental health problems than their ethnic majority counterparts. To understand what drives these negative outcomes, we integrate research on ethnic minorities at work with the job demands-resources (JDR) model. Based on the JDR model, we consider climate for inclusion as a key job resource for ethnic minority employees that mitigates the deleterious effects of ethnic minority status on job… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 123 publications
(166 reference statements)
0
4
0
Order By: Relevance
“…It is not entirely surprising that we report only a few significant indirect effects, given that we controlled for the previous levels of mediators and job satisfaction in the previous time point. This approach provides a more rigorous statistical test and sets a new standard for fairness research, making it more challenging to detect significant effects (Adamovic et al, 2023;Lang et al, 2011;Xu et al, 2023).…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…It is not entirely surprising that we report only a few significant indirect effects, given that we controlled for the previous levels of mediators and job satisfaction in the previous time point. This approach provides a more rigorous statistical test and sets a new standard for fairness research, making it more challenging to detect significant effects (Adamovic et al, 2023;Lang et al, 2011;Xu et al, 2023).…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…Manoharan and Singal (2017) suggested practices such as alternative access to job-related information (Nordsteien & Byström, 2018), assigning mentors with deeplevel similarity to newcomers (Zheng et al, 2021), intervention in newcomer-colleague conflicts (Nifadkar & Bauer, 2016), and fostering a caring climate (Thomas & Meglich, 2019). Several studies confirmed that inclusive practices can influence the relationships between employee-supervisor deep-level diversity and employee autonomy (Zheng et al, 2017), perceived discrimination and reactive aggression (Xiong et al, 2021), and diversity-caused depression systems and self-efficacy (Adamovic, Sojo, et al, 2022).…”
Section: Perceived Inclusive Practicesmentioning
confidence: 99%
“…However, prior studies revealed that little emphasis had been paid to stress management and coping strategies for female office workers. It is intended that a more balanced approach must be adopted to the stress problem that female employees face in the modern workplace to be more appropriately addressed (4) .…”
Section: Introductionmentioning
confidence: 99%
“…However, recently, employees have faced greater challenges as a result of the economy and working conditions. Therefore, it is essential to reduce occupational stress as much as possible before it leads to problems on the long run for the employees, particularly women employees (4) .…”
Section: Introductionmentioning
confidence: 99%